Multisystem Inflammatory Syndrome in Children and Adolescents (MIS-C) under the Setting of COVID-19: A Review of Clinical Presentation, Workup and Management. (June 2021) - Farooq, Ayesha; Alam, Fatima; Saeed, Asma; Butt, Farooq; Khaliq, Muhammad Azeem; Malik, Ayesha; Chaudhry, Manahil; Abdullah, Mohammad
Earlier in its course, SARS-CoV-2 was primarily identified to cause an acute respiratory illness in adults, the elderly and immunocompromised, while children were known to be afflicted with milder symptoms. However, since mid-April of 2020, latent effects of the virus have begun emerging in children and adolescents, which is characterised by a multisystem hyperinflammatory state; thus, the term Multisystem Inflammatory Syndrome in Children (MIS-C) was introduced by the WHO and CDC. The syndrome manifests itself approximately 4 weeks after COVID-19 infection, with symptoms mimicking Kawasaki Disease and Kawasaki Disease Shock Syndrome. Demographically, MIS-C peaks in children aged 5 to 14 years, with clusters in Europe, North and Latin America seen, later followed by Asia. Although the exact pathophysiology behind the syndrome is unknown, recent studies have proposed a post-infectious immune aetiology, which explains the increased levels of immunoglobulins seen in affected patients. Patient presentation includes, but is not limited to, persistent fever, rash, gastrointestinal symptoms and cardiac complications including myocarditis. These patients also have raised inflammatory markers including C reactive protein, ferritin and interleukin-6. In poorly controlled patients, the syndrome can lead to multiorgan failure and death. The mainstay of treatment includes the use of intravenous immunoglobulins, steroids, immune modulators and aspirin. Adjunct therapy includes the use of low molecular weight heparin or warfarin for long term anticoagulation. Currently very little is known about the syndrome, highlighting the need for awareness amongst healthcare workers and parents. Moreover, with increased cases of COVID-19 as a result of the second wave, it is essential to keep MIS-C in mind when attending patients with a past history of COVID-19 exposure or infection. Additionally, once these patients have been identified and treated, strict follow-up must be done in order carry out long term studies, and to identify possible sequelae and complications.